Identification of the number of home accidents per year involving children in the 0-6 age group and the measures taken by mothers to prevent home accidents - Erkal, Sibel (The Turkish Journal of Pediatrics, 2010)
This study was designed and carried out to determine the factors effective on the home safety measures taken by mothers with children in the 0-6 age group and to detect the frequency of home accidents among children in this group. The study was carried out with the participation of 514 mothers who were registered at the H. Ulgen Health Center affiliated with the Directorate of Mamak Health Group. The study data were collected through a questionnaire form and the "Scale for Identification by Mothers of the Safety Measures Taken by Mothers to Prevent Home Accidents in Children in the 0-6 Age Group". It was found that 37.9% of the 0-6 age group children had had a home accident, with "fall" the most common (75.4%). A statistically significant difference was recorded in the mother’s total mean score from the scale with respect to the factors of educational status, age, family type, and number of children (p < 0.05).